Organic-Free Synthesis of Finned Mordenite Zeolite - Lima, Rafael C. (2022)
Mordenite is a well-known zeolite widely used for industrial processes. However, its pore architecture can be inconvenient due to diffusional issues. A study of the synthesis parameters from an organic-free dense gel was carried out to control the crystal morphology, which resulted in finned mordenite zeolite particles. The obtained materials were characterized by XRD, FTIR, 29Si and 27Al MAS-NMR, elemental analysis, nitrogen physisorption, SEM, and TEM. We found that careful manipulation of the hydrothermal parameters directly affected the sizes and morphologies of the crystallites and particles, as well as the textural properties of the final products. Additionally, it was found that mordenite could exhibit a fin morphology with additional mesoporosity, which is a promising means to reduce the diffusional problems of one-dimensional-channel zeolites.